Slovenski pisatelj Razvoj vloge literarnega proizvajalca v slovenskem literarnem sistemu - Dović, Marijan (Studia litteraria, 2007)
This monograph deals with theoretical and historical aspects of the position of the writer in Slovenia from the end of 18th century, when literature started to differentiate itself from other systems and form an autonomous social system, to the situation in which the writer finds himself at the beginning of the 21st century.